2014
DOI: 10.22146/majkedgiind.8750
|View full text |Cite
|
Sign up to set email alerts
|

Implant Gigi One-Piece vs Two-Pieces dalam Praktek Sehari-Hari

Abstract: Saat ini, implant merupakan pilihan terbaik untuk menggantikan gigi yang tanggal, akan tetapi prosedur pemasangannya terbilang rumit dan memerlukan prosedur bedah kedua untuk pemasangan prostetik. Beberapa komplikasi seperti screw patah atau longgar dan adanya celah mikro pada batas pertemuan implant dan abutment dapat menyebabkan kegagalan implant. Studi kasus ini bertujuan untuk membahas mengenai keuntungan dan kerugian desain implant gigi one-piece dan two-pieces. Kasus pertama, seorang wanita berusia 43 ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
2
Order By: Relevance
“…In this study, a one-piece implant type was utilized, where the abutment is integrated with the implant, forming a single unit. In its application, this implant is inserted into the bone with the abutment part positioned above the gingiva (nonsubmerged) [14]. The implant specimens are mounted on a holder with a 30-degree off-axis inclination, following the standards for fatigue testing on implants and abutments (ISO 14801) to simulate the worst-case scenario of implant placement, including the method used in "All-on-four" implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a one-piece implant type was utilized, where the abutment is integrated with the implant, forming a single unit. In its application, this implant is inserted into the bone with the abutment part positioned above the gingiva (nonsubmerged) [14]. The implant specimens are mounted on a holder with a 30-degree off-axis inclination, following the standards for fatigue testing on implants and abutments (ISO 14801) to simulate the worst-case scenario of implant placement, including the method used in "All-on-four" implant placement.…”
Section: Discussionmentioning
confidence: 99%
“…Kurnia et al . [ 14 ] evaluated the advantages and disadvantages of OPI and TPI based on two cases, and they concluded that the lack of a micro gap in a OPI was better in preventing crestal bone resorption.…”
Section: Discussionmentioning
confidence: 99%
“…Terdapat pula kasus ekstraksi gigi yang dapat menyebabkan kerusakan tulang alveolar cukup besar sehingga membutuhkan waktu sekitar 4 bulan hingga jaringan keras dan jaringan lunaknya siap untuk dipasang implan. 2 Ditemukan juga beberapa kasus ekstraksi pada gigi anterior seperti gigi caninus, tidak hanya menyebabkan kesulitan dalam mengunyah makanan, namun juga dapat mengganggu fungsi estetika pada pasien. Sebaiknya, kehilangan gigi anterior ini harus segera dilakukan perawatan rehabilitas, seperti diberikan implan.…”
Section: Pendahuluanunclassified